Genome-Wide Identification and Expression Analysis of the VILLIN Gene Family in Soybean - Yueqiong Zhou; Liangliang He; Shaoli Zhou; Qing Wu; Xuan Zhou; Yawen Mao; Baolin Zhao; Dongfa Wang; Weiyue Zhao; Ruoruo Wang; Huabin Hu; Jianghua Chen (Plants, 2023)
The VILLIN (VLN) protein is an important regulator of the actin cytoskeleton, which orchestrates many developmental processes and participates in various biotic and abiotic responses in plants. Although the VLN gene family and their potential functions have been analyzed in several plants, knowledge of VLN genes in soybeans and legumes remains rather limited. In this study, a total of 35 VLNs were characterized from soybean and five related legumes. Combining with the VLN sequences from other nine land plants, we categorized the VLN gene family into three groups according to phylogenetic relationships. Further detailed analysis of the soybean VLNs indicated that the ten GmVLNs were distributed on 10 of the 20 chromosomes, and their gene structures and protein motifs showed high group specificities. The expression pattern analysis suggested that most GmVLNs are widely expressed in various tissues, but three members have a very high level in seeds. Moreover, we observed that the cis−elements enriched in the promoters of GmVLNs are mainly related to abiotic stresses, hormone signals, and developmental processes. The largest number of cis−elements were associated with light responses, and two GmVLNs, GmVLN5a, and GmVLN5b were significantly increased under the long light condition. This study not only provides some basic information about the VLN gene family but also provides a good reference for further characterizing the diverse functions of VLN genes in soybeans.